THE ROLE OF PROFITABILITY AS A CHANNEL ON INFLUENCING THE EFFECT OF MACROECONOMICS ON STOCK RETURNS IN THE INDONESIAN STOCK EXCHANGE DURING THE COVID-19 PANDEMIC - Sri Hermuningsih; Fatimah Kari; Anisya Dewi Rahmawati; Final Prajnanta (International Journal of Business and Society, 2024)
The purpose of this study is to examine the factors that influenced stock returns during the COVID-19 pandemic in Indonesia, with profitability functioning as an intervening variable. It acts as a mediating variable, influencing how macroeconomic factors impact a company’s stock returns. Companies with higher profitability can withstand macroeconomic impacts, leading to higher returns. It is crucial for a company to avoid rising stock returns and ensure stability. The population in this study is the consumer goods industry listed on the Indonesia Stock Exchange. The research sample consists of the consumer goods industry from 2020 to 2022.Sampling uses purposive sampling with data from 26 companies and 312 quarterly financial report data. Test the hypothesis using SmartPLS. The study reveals that exchange rates, interest rates, and inflation all negatively impact stock returns, with profitability acting as an intervening variable. Additionally, inflation also negatively impacts stock returns. This research implies that exchange rate stability is essential for companies carrying out export-import activities as a means of transaction in trade. The increase in interest rates encourages investors to continue investing in stocks because they are temporary and will return to their original level. Understanding the role of profitability in the relationship between macroeconomic factors and stock performance can help investors make more informed decisions.